Catalytic decarboxylation of non-edible oils over three-dimensional, mesoporous silica-supported Pd - Raut, Ravindra; Banakar, Vikram V.; Darbha, Srinivas (Journal of Molecular Catalysis A-Chemical, 2016)
Deoxygenation of fatty acids (oleic and stearic acids) and non-edible oil (jatropha oil) over Pd(1-5 wt%) supported on two structurally different, three-dimensional, mesoporous silica (SBA-12 and SBA-16) catalysts was investigated. Pd/SBA-16 (cubic mesoporous structure with space group Im (3) over barm) showed higher catalytic activity than Pd/SBA-12 (hexagonal mesoporous structure with space group p6(3)/mmc). The influence of reaction parameters like temperature, H-2 pressure and Pd content as well as the nature of the feedstock on catalytic activity and product selectivity was studied. A temperature of above 320 degrees C, reaction time of 5 h and Pd content (on silica surface) of 3 wt% enabled complete conversion of the fatty compounds into diesel-range hydrocarbons. Deoxygenation proceeded through hydrodeoxygenation and decarboxylation mechanisms when a saturated (stearic) acid was used as a feed while it advanced mainly through decarboxylation route when an unsaturated (oleic) acid was employed. Higher surface hydrophobicity and smaller size particles of Pd are the possible causes for the superior catalytic activity of Pd/SBA-16. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Biofuel; Deoxygenation; Diesel-range hydrocarbons; Mesoporous silica; Supported palladium; Vegetable oil